Kajian Hukum Terhadap Peraturan Desa Kradenan Kecamatan Kaliwungu Kabupaten Semarang No. 11 Tahun 2022 Tentang Pungutan Pasar Desa - Warsito, Warsito; Destyarini, Normalita; Prastyanti, Rina Arum; Elisanti, Evi (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this research is to determine the process of formation and legal consequences of Kradenan Village Regulations, Kaliwungu District, Semarang Regency No. 11 of 2022 concerning Village Market Levies. The research subjects were traders at Kradenan Village's Firm Market. The research method used is an empirical juridical approach. Data collection techniques are literature study, interviews, observation and documentation. The qualitative descriptive data analysis technique is in the form of an interactive analysis model. The results of the research show that the process of forming village regulations regarding village market levies is 1) village regulations are determined by the village head with the BPD, 2) hamlet deliberation 3) village deliberation, 4) village head conveys village regulations to the regent or mayor through the subdistrict head as a supervisory control or coaching, 5) Village government and BPD disseminate information regarding Kradenan Village regulations, Kaliwungu District, Semarang Regency No. 11 of 2022 concerning village market levies on the community and stakeholders. The legal consequences of village regulations regarding village market levies are warning sanctions and administrative sanctions for violations and non-compliance with these regulations. The conclusion of the research is that the impact of village regulations regarding village market levies is very significant in increasing PAD, empowering village-owned assets, prospering and improving the economy of village communities. To optimize PAD, it needs to be determined and regulated in village market levies